1997
DOI: 10.1111/j.1398-9995.1997.tb01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with partially purified and standardized tree pollen extracts. IV. Results from long‐term (6‐year) follow‐up

Abstract: The long-term effect of tree pollen extract immunotherapy was investigated 6 years after termination of the treatment. Subjective symptom evaluation of 36 patients 6 years after a 3-year period of immunotherapy showed that rhinitis and asthma symptoms remained at the improved level reached just after termination of the treatment. Some 86% of the rhinitis patients and 68% of the asthma patients maintained improvement. None of the rhinitis patients developed asthma in the study period. Skin prick tests reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 26 publications
3
72
0
6
Order By: Relevance
“…Previous studies showed a reduction in long-term asthma risk among allergic rhinitic patients treated with SIT [68,69]. Meta-analyses show that this treatment could be beneficial in pollen-induced rhinitis and asthma, but state that more investigations are needed to determine its efficacy in house dust mite allergy [70].…”
Section: Treatmentmentioning
confidence: 99%
“…Previous studies showed a reduction in long-term asthma risk among allergic rhinitic patients treated with SIT [68,69]. Meta-analyses show that this treatment could be beneficial in pollen-induced rhinitis and asthma, but state that more investigations are needed to determine its efficacy in house dust mite allergy [70].…”
Section: Treatmentmentioning
confidence: 99%
“…The most pronounced serological marker of successful vaccination is a 30-to 100-fold increase in allergenspecific IgG (11,12), whereas there is no substantial change in IgE comparing pre-and posttreatment (6). Furthermore, as shown for pollen allergy, the treatment gradually attenuates the seasonal rise in IgE (11) and leads to a seasonal rise in IgG, particularly IgG 4 (13).…”
mentioning
confidence: 99%
“…A link between allergic rhinitis and atopic asthma has been demonstrated in numerous epidemiological studies. It is reported that 25 to 43 % of the patients experiencing rhinitis naturally develop asthma within 10 years (21,22), whereas in the study by Jacobsen et al, (14) none of the patients with allergic rhinitis developed asthma over a sixyear period following the termination of immunotherapy.…”
Section: Discussionmentioning
confidence: 72%
“…This mechanism of action has been unique, and different from any other pharmacological treatment in many respects. First, SIT can modify the natural history of allergic disease, as confirmed in rigorously conducted trials (13,14). Second, SIT can prevent the onset of new sensitizations, as demonstrated clearly in children in several studies (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation